The Influence Of Social Media, Financial Literacy, Self-Control And Financial Attitudes On Financial Behavior (Student Of The Faculty Of Economics Univ. Sarjanawiyata Tamansiswa) - Yetti Saripah; Risal Rinofah; Pristin Prima Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Abstract The purpose of this research was to examine and explain the influence of social media, financial literacy, and self-control on financial behavior in the study of students of the Faculty of Economics, Tamansiswa University, Yogyakarta. This research was conducted on students of the Faculty of Economics, Universitas Bachelor of Law Tamansiswa using the lemesslow formula with a sample size of 96 respondents who used statements for each variable via Google form for questionnaires that were distributed to students. The results of the study show that social media and control have no influence on financial behavior, while financial literacy and financial attitudes have a positive and significant influence on financial behavior.